An interference iterative reconstruction algorithm based on a single off-axis digital hologram. (February 2023) - Wang, Fengpeng; Fan, Feifan; Wang, Dayong; Yao, Jia; Zhu, Yanling
Highlights: We propose an interference iterative algorithm (IIA) for the reconstruction of a single off-axis hologram. Interference and inverse interference processes are used to extract the object wave from the off-axis hologram. A filter with increasing radius is used to improve the competitive advantage of low frequency information in the early iterations. Abstract: Compared with in-line digital holography, off-axis digital holography can be used to image more kinds of objects without the limitation of weak phase and sparsity, but the resolution is lower. In this paper, we put forward a high-resolution iterative reconstruction algorithm for off-axis holography which requires only the recording of a single off-axis hologram. Interference and inverse interference processes are used to extract the object wave from the off-axis hologram. A frequency domain filter with increasing radius is used to improve the competitive advantage of low frequency information in the early iterations, while retaining the high frequency information. The constraints of total variation and positive absorption are implemented at the object plane to enhance the robustness of the algorithm. Numerical simulations and experiments show that the resolution of our method is higher than traditional off-axis digital holography. In addition, it is suitable for phase image when the object has a strong phase fluctuation, as well as for imaging dynamical objects.